The Inspectorate of Education and the assessment of permanent formation of school teachers - Antúnez Marcos, Serafín (Avances en Supervisión Educativa, 2009)
The Inspectorate of Education and the assessment of permanent formation of School Teachers. There is a great deal of uncertainty when trying to assess the usefulness and efficiency of the programmes for the permanent formation of school teachers. This uncertainty becomes a common concern to every agency committed to the improvement of education. It is a general wish to know how useful the integrated knowledge and resources suite devoted to permanent formation is in order to ensure that this improvement eventually reaches the school classrooms and the students’ learning process.